Healthcare Team Members' Views on Social Determinants of Health Screening and Referral Practices in a Pediatric Emergency Department - Jadelynn Nagy; Natalie Tedford; Sahlil Ahmed; Sofia Thoms; Akiko Kamimura; Maija Holsti (The Beryl Institute, 2024)
We aimed to explore the healthcare team members' (HTMs) views on social determinants of health (SDH) screening and referral processes in a pediatric emergency department (PED). We conducted a cross-sectional, mixed-methods study to explore PED HTMs' views on social care practices at a quaternary-level children's hospital. The survey was created using a goal identification framework. The survey gathered quantitative and qualitative data by assessing SDH screening practices, comfort and personal habits in screening, prioritization of SDH domains, workflows to perform screening, and perceived barriers to screening. Quantitative data were analyzed using descriptive statistics. Qualitative data were analyzed using thematic analysis and multiple reviewers to identify themes in free-text responses. There were 63 HTMs (48% response rate, Table 1), all of whom reported SDH screening efforts should continue in the PED (Fig. 1), yet 36% were unaware of the current SDH screening processes. Participants reported a median comfort level rate of 47.5 out of 100 when asking SDH-related questions (Fig. 1), and the highest reported barriers were "lack of knowledge/skill on resources" (77.3%), "lack of time" (68%), and "patient volume" (59%) (Fig. 2). Regarding the screening process, approximately half of the respondents suggested improvements in "integration of screening" and "variability of screening" (Fig. 4). This explorative analysis demonstrated that HTMs support continuing screening and referring patients for SDH-related needs. In addition, HTM survey respondents suggested improvements in screening and referral processes, opportunities for HTM training, and screening support to address social needs and ultimately improve patient health outcomes.